Enhances Security on Fraud in the Auditors of BPKP Province North Sumatra - Rahima Br. Purba; Faisal Adrian Nasution (Budapest International Research and Critics University, 2021)
This study aims to test and analyze the factors that influence the ability of auditors to detect fraud at Financial and Development Supervisory Agency (BPKP) auditors in provinces North Sumatra. This type of research is a causal associative population and a sample of 34 Auditor Functional Officials in the Regional Government Accountability Sector (APD) in the BPKP Representative Office of North Sumatra Province. The data collection technique in this study was a questionnaire. A method of data analysis using data analysis tests, classical assumptions, and hypotheses. The results showed that Competence and Professional Ethics have a positive and significant effect on the ability to detect fraud, while Independence and Professional Skepticism do not affect the ability to detect fraud at the BPKP Representative Office of North Sumatra Province. Independence, Competence, Professional Ethics, and Professional Skepticism have a simultaneous effect on the ability to detect fraud at the Finance and Development Supervisory Agency (BPKP) Representative Office of North Sumatra Province